A systematic review of randomised controlled trials of non-pharmacological pain relief strategies for pregnant women in labour - Abelgas, Marjorie Caroline (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MCur)--University of Stellenbosch, 2011.